Investigating Accountability in Business-intensive Systems-of-Systems - Cordeiro, Felipe; Vasconcelos, Aline; Santos, Rodrigo Pereira dos; Lago, Patricia (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de Software, 2024)
CONTEXT: The evolution of business processes has driven the integration of systems-of-systems (SoS) across various domains, leveraging technologies such as cloud computing, e-commerce platforms, and smart environments. In this context, the integration of various heterogeneous and independent constituents systems include information systems that collaborate to achieve business goals. Hence, the accountability of these systems must be a concern, but traditional accountability approaches can obscure the responsibility and ownership of data, processes, and outcomes. PROBLEM: This complexity often results in studies offering specific solutions, then highlighting the ongoing need for a shared understanding of accountability. Furthermore, establishing accountability as a quality requirement poses a significant challenge due to limited research and an undefined agenda for underlying challenges. SOLUTION: This paper presents an overview of accountability from reporting on the current landscape to proposing a research agenda to address existing challenges. METHOD: The study adopts a prescriptive approach based on a systematic mapping study. RESULTS: The study yields insights into accountability, and a research agenda when identifying seven topics for further investigation. CONCLUSION: By consolidating knowledge on accountability, this study facilitates the expansion of the body of knowledge on the field and brings new inquiry to inspire innovative solutions.